The Impact of Transportation Disruptions, Port Congestion, and Freight Restrictions on the Distribution Capability of Indonesian Footwear Supplier - Hally Hanafiah; Tony Kristhiofan; Indri Saputri (Department of Ocean Engineering, Faculty of Engineering, Hasanuddin University, 2026)
The Trump-era tariffs caused significant disruptions to global maritime supply chains, disproportionately affecting export-dependent archipelagic nations. This study investigates the impact of tariff-induced maritime shocks specifically port congestion, transportation delays, and freight restrictions—on the distribution capabilities of Indonesian footwear suppliers. While previous literature broadly addresses general supply chain risks, this research isolates how these specific maritime bottlenecks translate to supplier-level operations within buyer-driven value chains. Utilizing a quantitative PLS-SEM approach on survey data from 50 tier-1 Indonesian suppliers, the analysis reveals counterintuitive findings. Contrary to expectations, systemic freight restrictions positively catalyzed distribution capabilities by forcing strategic adaptation. Furthermore, port congestion and transportation disruptions yielded non-significant negative effects, suggesting that centralized maritime governance such as FOB contracts buffers suppliers from direct operational shocks while simultaneously enforcing structural dependency. These findings extend maritime logistics literature by highlighting how governance arrangements, rather than just physical constraints, dictate supplier resilience during global trade disruptions.